2020
DOI: 10.21203/rs.3.rs-15666/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lung cancer awareness and palliative care interventions implemented in Africa: A systematic scoping review’

Abstract: Background: Lung cancer is the most common cancer and cause of cancer-related deaths, responsible for nearly one in five deaths across the globe. In low and middle-income countries (LMICs), lung cancer is often diagnosed at a late stage due to poor public knowledge and awareness of the signs and symptoms of lung cancer. It is believed that increasing the awareness about lung cancer is key to reducing the diagnosis and treatment delays. Early implementation of palliative care has also been reported to improve a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…An England study demonstrated increases in the public's recognition of persistent coughing as a symptom of lung cancer, together with prompt referrals of suspected lung cancer patients by GPs, and lung cancer diagnoses (43). As demonstrated by recent systematic and scoping reviews, no intervention studies have been conducted in the African region recently (44,45). The South African referral pathways and use of public health sector facilities trends introduce delays in the diagnosis of lung cancer (1,46).…”
Section: Lung Cancer Awareness Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…An England study demonstrated increases in the public's recognition of persistent coughing as a symptom of lung cancer, together with prompt referrals of suspected lung cancer patients by GPs, and lung cancer diagnoses (43). As demonstrated by recent systematic and scoping reviews, no intervention studies have been conducted in the African region recently (44,45). The South African referral pathways and use of public health sector facilities trends introduce delays in the diagnosis of lung cancer (1,46).…”
Section: Lung Cancer Awareness Interventionsmentioning
confidence: 99%
“…They perform various duties, which have led them to be classified either as generalists or disease-specific CHWs (44). In South Africa, they have been an invaluable component of healthcare teams since the early 1930s (45). Their roles and duties have been variously defined as that of treatment defaulter and contact tracing, screening, condom distribution, and participating in community campaigns, especially in the prevention and control of human immune-deficiency virus (HIV) and tuberculosis (TB) (37,46).…”
Section: Introductionmentioning
confidence: 99%